The impact of department chair leadership identity on faculty thriving in comprehensive university reform: the cross-level moderating role of work arrangement flexibility - Gou, Jinan; Shen, Yuzhao (Frontiers in Psychology, 2026)
IntroductionAs universities undergo intensifying reform pressures, department chairs face the challenge of balancing administrative duties with academic mentorship; how they internalize their leadership role—their leadership identity—may critically shape faculty outcomes, yet this internal driver remains underexplored.MethodsUsing a multi-source, two-stage design, paired data were collected from 60 department chairs and 250 faculty members across 10–14 universities undergoing “Double First-Class” reform.ResultsHierarchical linear modeling results reveal that transformational leadership significantly shapes leadership identity, which in turn exerts a positive cross-level effect on faculty thriving. Psychological empowerment partially mediates this relationship. Furthermore, work arrangement flexibility significantly moderates the leadership identity–psychological empowerment relationship, with stronger positive effects under high-flexibility conditions.DiscussionThis study makes three contributions: (1) shifting leadership research focus from overt behavior to leaders’ self-concept as a driver of effectiveness; (2) enriching social information processing theory by demonstrating how internal identity becomes a perceivable cross-level social cue; and (3) providing practical implications for universities to cultivate department chairs’ leadership identity and implement flexible work policies that enhance faculty wellbeing during organizational transformation.